Site-Specific Neutrophil Migration and CXCL2 Expression in Periodontal Tissue. (July 2016) - Greer, A.; Irie, K.; Hashim, A.; Leroux, B.G.; Chang, A.M.; Curtis, M.A.; Darveau, R.P.
The oral microbial community is the best-characterized bacterial ecosystem in the human host. It has been shown in the mouse that oral commensal bacteria significantly contribute to clinically healthy periodontal homeostasis by influencing the number of neutrophils that migrate from the vasculature to the junctional epithelium. Furthermore, in clinically healthy tissue, the neutrophil response to oral commensal bacteria is associated with the select expression of the neutrophil chemokine CXCL2 but not CXCL1. This preliminary study examined the contribution of commensal bacteria on neutrophil location across the tooth/gingival interface. Tissue sections from the root associated mesial (anterior) of the second molar to the root associated distal (posterior) of the second molar were examined for neutrophils and the expression of the neutrophil chemokine ligands CXCL1 and CXCL2. It was found that both the number of neutrophils as well as the expression of CXCL2 but not CXCL1 was significantly increased in tissue sections close to the interdental region, consistent with the notion of select tissue expression patterns for neutrophil chemokine expression and subsequent neutrophil location. Furthermore, mice gavaged with either oral Streptococcus or Lactobacillus sp. bacteria induced a location pattern of neutrophils and CXCL2 expression similar to the normal oral flora. These data indicate for the first time select neutrophil location and chemokine expression patterns associated with clinically healthy tissue. The results reveal an increased inflammatory load upon approaching the interproximal region, which is consistent with the observation that the interproximal region often reveals early clinical signs of periodontal disease.